Accounting information in financial statements of Malaysia's listed companies : application of factor analysis. - Chan, Mei Ling. (2008)
This project aims to analyze the underlying structure of the vast multitude of variables derived from financial statements of 105 companies listed on KLSE and reduced them into a parsimonious set of factors that accounted for 70.06% of the information contained in these variables. The factors are interpreted as Size/Growth, Solvency, Profitability, Liquidity and Sales Efficiency.